Mitigating amphibian chytridiomycosis with bioaugmentation: characteristics of effective probiotics and strategies for their selection and use. (3rd March 2013) - Bletz, Molly C.; Loudon, Andrew H.; Becker, Matthew H.; Bell, Sara C.; Woodhams, Douglas C.; Minbiole, Kevin P. C.; Harris, Reid N.; Gaillard, Jean‐Michel
Abstract Probiotic therapy through bioaugmentation is a feasible disease mitigation strategy based on growing evidence that microbes contribute to host defences of plants and animals. Amphibians are currently threatened by the rapid global spread of the pathogen, Batrachochytrium dendrobatidis (Bd), which causes the disease chytridiomycosis. Bioaugmentation of locally occurring protective bacteria on amphibians has mitigated this disease effectively in laboratory trials and one recent field trial. Areas still naïve to Bd provide an opportunity for conservationists to proactively implement probiotic strategies to prevent further amphibian declines. In areas where Bd is endemic, bioaugmentation can facilitate repatriation of susceptible amphibians currently maintained in assurance colonies. Here, we synthesise the current research in amphibian microbial ecology and bioaugmentation to identify characteristics of effective probiotics in relation to their interactions with Bd, their host, other resident microbes and the environment. To target at‐risk species and amphibian communities, we develop sampling strategies and filtering protocols that result in probiotics that inhibit Bd under ecologically relevant conditions and persist on susceptible amphibians. This filtering tool can be used proactively to guide amphibian disease mitigation and can be extended to other taxa threatened by emerging infectious diseases.